Lethal Borna disease virus 1 infections of humans and animals – in-depth molecular epidemiology and phylogeography - Ebinger, Arnt; Santos, Pauline D.; Pfaff, Florian; Dürrwald, Ralf; Kolodziejek, Jolanta; Schlottau, Kore; Ruf, Viktoria; Liesche-Starnecker, Friederike; Enßer, Armin; Korn, Klaus; Ulrich, Reiner; Fürstenau, Jenny; et al. (Nature Communications, 2024)
Borna disease virus 1 (BoDV-1) is the causative agent of Borna disease, a fatal neurologic disorder of domestic mammals and humans, resulting from spill-over infection from its natural reservoir host, the bicolored white-toothed shrew (Crocidura leucodon). The known BoDV-1-endemic area is remarkably restricted to parts of Germany, Austria, Switzerland and Liechtenstein. To gain comprehensive data on its occurrence, we analysed diagnostic material from suspected BoDV-1-induced encephalitis cases based on clinical and/or histopathological diagnosis. BoDV-1 infection was confirmed by RT-qPCR in 207 domestic mammals, 28 humans and seven wild shrews. Thereby, this study markedly raises the number of published laboratory-confirmed human BoDV-1 infections and provides a first comprehensive summary. Generation of 136 new BoDV-1 genome sequences from animals and humans facilitated an in-depth phylogeographic analysis, allowing for the definition of risk areas for zoonotic BoDV-1 transmission and facilitating the assessment of geographical infection sources. Consistent with the low mobility of its reservoir host, BoDV-1 sequences showed a remarkable geographic association, with individual phylogenetic clades occupying distinct areas. The closest genetic relatives of most human-derived BoDV-1 sequences were located at distances of less than 40 km, indicating that spill-over transmission from the natural reservoir usually occurs in the patient´s home region.
CRIS-Team Scopus Importer:2024-09-20